Hydrocracking of gas oil using USY-zeolite-based catalyst - Alsobaai, Ahmed Mubarak; Bassim, H. Hameed; Ridzuan, Zakaria (2006)
The conversion of petroleum gas oil to transportation fuels was investigated using NiMo, CoMo, NiW and CoW catalysts supported on commercial USY zeolite. The catalysts were prepared using the incipient wetness method. The reaction was carried out in a high-pressure shaking reactor at reaction temperature of 450 oC, contact time of 90 minutes and catalyst to sample ratio of 0.04. It was found that over NiW/USY catalyst, the values of total conversion and yield of total distillate fuels were 64.35 and 54.12 wt%, respectively, compared to 46.48 and 38.25 wt% over unloaded USY zeolite. The hydrocracking activities of other USY-based catalysts were increased as follows, from most active to least active: NiW/USY> NiMo/USY> CoW/USY > CoMo/USY > USY. The catalysts were characterized by TGATPD acidity, TGA thermal stability, and BET surface-area measurements.